Poly(3-hydroxybutyrate) production from natural gas by a methanotroph native bacterium in a bubble column bioreactor - Khosravi-Darani, Kianoush (Array, 2019)
Reducing the total cost of poly(3-hydroxybutyrate) (PHB) production as an attractive substitute for conventional petrochemical plastics still remains an unsolved problem. The aim of this research was the screening of PHB-producing microorganisms and selection of the best suitable medium for microbial growth and PHB production from methane. A new isolated methanotroph for PHB production from natural gas was studied in different media. After selection of the suitable medium, the effect of five process variables (content of nitrogen source, disodium hydrogen phosphate, methane to air ratio, seed age, and pH) on PHB production was investigated in a bubble column bioreactor. Also, hydrodynamic and mass transfer factors (flow regime, mixing time, gas hold up, and kLa) were considered. At optimum operating conditions and engineering parameters in a bubble column, PHB content in the dried biomass reached 25 % w/w. The results showed that pH is the most important variable in the selected conditions.